Study on GC-MS fingerprint of petroleum ether fraction of Shenqi Jiangtang Granules - Li Bingbing; Wang Qian; Li Caixia; Huang Wenjing; Chen Guoliang; Guan Yongxia; Muhammad Ishaq; Xiao Xue; Yan Shikai (KeAi Communications Co., Ltd., 2021)
Objective: To establish gas chromatography-mass spectrometry (GC-MS) fingerprint method for the petroleum ether fraction of Shenqi Jiangtang Granules (SQJTG) and evaluate the product quality. Methods: The GC-MS fingerprint of petroleum ether fraction of SQJTG was established by GC-MS, and the chemical components corresponding to the fingerprint peaks were structurally identified on NIST2014. The batch consistency of SQJTG products was evaluated based on the chemical composition of petroleum ether parts by using fingerprint similarity evaluation and Principal components analysis (PCA) technology. At the same time, Hotelling's T2 and DMODX statistics are used to set the control range for the quality of different batches of products. Results: Twenty-two components were identified from the petroleum ether part of SQJTG, accounting for 60.94% of the total components separated. The similarity of fingerprints of petroleum ether parts of 24 batches of SQJTG was greater than 0.95. The PCA of 24 batches of samples were all under the control limits of Hotellin's T2 and DMODX statistics, indicating that the petroleum ether parts of different batches of SQJTG were consistent. Conclusion: The developed GC-MS fingerprint method can be used to evaluate the quality of SQJTG.